RDA in the Fifth Information Age - Dunsire, Gordon (Organizacija znanja, 2023)
The Fifth Information Age is characterised by the ubiquitous recording of social transactions in an explosion of persistent cultural memory. A person who contributes to social media is an agent who creates digital cultural artefacts. The internet of things, of personal devices for the capture, creation, transmission, and output of information means everyone is potentially an author, a publisher, a distributor, with a profound impact on traditional methods of authority control. The focus of authority control is shifting from the provision of a unique label for an individual person or group to the description of an individual as an instance of a class, as an entity. This paper will discuss some of the issues in entity-based cataloguing and the tools provided to resolve and accommodate them in RDA: Resource Description and Access. These include the implementation of entities and relationships defined in the IFLA Library Reference Model; the categorization of entity labels as unstructured, structured, and identifier strings; and the development of implementation scenarios to encompass linked open data. The infrastructure that allows any person to be the creator of a cultural resource also allows any person to describe the resource; everyone is potentially a cataloguer, a metadata creator. The paper describes the general approach to metadata provenance that is provided in RDA and how it can be used to authenticate metadata from a wide variety of sources, including crowdsourcing, and the application of automatic data inferencing to interoperate metadata from multiple sources.
Keywords: bibliografska kontrola; bibliographic control; družbeni mediji; opis virov; resource description; social media; standardi; standards